2014
DOI: 10.1161/hypertensionaha.114.03837
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Inhibition of Endothelin-1 Release in the Vasculature

Abstract: A key function of endothelial derived nitric oxide (NO) is to limit the constrictor capacity of endothelin (ET)-1.1,2 Thus, an imbalance between NO and ET-1 can result in ET-1-dependent increased vascular tone.1 Indeed, the importance of sustained, NO inhibition of the ET-1 drive to increase tone is exemplified in vivo by the rapid, ET-1-mediated arterial pressure elevation after acute NO synthase (NOS) inhibition. Moreover, the ET-1 pressor effect after NOS inhibition is independent of other pressor systems a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 86 publications
1
18
0
1
Order By: Relevance
“…Endothelial nitric oxide synthase is constitutively active, generates NO in response to shear stress and other physiologic stimuli and can limit the constrictor action of ET-1. This has recently been reviewed ( Rapoport, 2014 ). A number of pathophysiological conditions are associated with endothelial cell dysfunction and loss of nitric oxide.…”
Section: Classification Of Selective Agonists and Antagonistsmentioning
confidence: 99%
“…Endothelial nitric oxide synthase is constitutively active, generates NO in response to shear stress and other physiologic stimuli and can limit the constrictor action of ET-1. This has recently been reviewed ( Rapoport, 2014 ). A number of pathophysiological conditions are associated with endothelial cell dysfunction and loss of nitric oxide.…”
Section: Classification Of Selective Agonists and Antagonistsmentioning
confidence: 99%
“…Therefore, NO and ET are used as biomarkers to reflect the function of endothelial cells (22). In CIN models, the expression of ET is downregulated, leading to vasoconstriction (23). The results demonstrated that both iopamidol and iodixanol upregulate ET levels, indicating that the two CMs are able to induce injury in endothelial cells.…”
Section: Discussionmentioning
confidence: 97%
“…In our model, myogenic oscillations were phenomenologically considered as forcing tension applied to the vessel wall from VSMs. The model phenomenologically takes into account the modulation of SMC activity by vascular endothelium signaling (Koenigsberger et al, 2005; Delgado et al, 2010; Rapoport, 2014). One of the molecular mechanisms of this modulation may be explained through the release of vasoactive substances such as e.g., nitric oxide and/or Endotheli-1 expression as a result of activation of mechanosensitive channels in response to the shear stress (Vallance and Hingorani, 1999).…”
Section: Discussionmentioning
confidence: 99%